Transitivity of Educational Environment of Modern Russian School as Psychological and Educational Problem - A. D. Andreyeva (Научный диалог)
The article is devoted to the problem of the functionality of the modern school educational environment, its readiness to solve its main social problems in the conditions of multiple and rapid transformations of material and social conditions of society. The necessity of reforming the education system, searching for new approaches in preparing children for productive functioning in unstable socio-cultural systems is emphasized. It is noted that the current new educational standard meets the ideology of modernization and sets targets for the preservation of the functionality of the education system, its ability to meet the requirements of a transitive society striving for development. It is shown that the practical reconstruction of national education is dominated by the traditionalist tendencies that are contrary to the idea of modernity, which testifies to transitive character of the educational environment of the school. The results of empirical study of psychological and pedagogical problems of modern school from the perspective of all participants of the educational process are presented. There are significant differences in the attitude of the family and the school to the reformation of school education, due to the leading social needs of different groups of the population. The contradictions between two social institutions responsible for preparing children for future life reflect the transitive nature of the educational environment of today’s school, striving simultaneously for the modernization and restoration of traditional models of education and upbringing of children.